Africana womanism et homosexualité dans Crépuscule du tourment 1 de Léonora Miano - Ndi Etondi, Vanessa (Études littéraires africaines, 2019)
Dans Crépuscule du tourment 1 de Léonora Miano, que ce soit dans le « Nord » ou sur le « Continent » subsaharien, l’Afropéenne Ixora lutte pour imposer sa triple marginalité : femme, noire, homosexuelle. Dans la démarche migratoire qu’elle accomplit pour offrir un avenir déracialisé à son fils, Ixora finit par trouver l’amour saphique sous le soleil homophobe des tropiques. L’article analyse la complexité de ce personnage à travers l’approche intersectionnelle de Clenora Hudson-Weems. Élaboré pour circonscrire les facteurs d’oppression de la femme noire, l’africana womanism dénonce successivement le racisme, le classisme et le sexisme. Si le parcours d’Ixora rejoint en partie la théorie de C. Hudson-Weems, il permet aussi de la dépasser et de proposer une image plus libre de la femme noire contemporaine.
http://www.apela.fr/
Keywords: africana womanism; afro-féminisme; approches et analyses; arts; discipline; femmes* noires; féminisme africain; homosexualité; littérature; ressource en ligne; sexualité; thématiques; études littéraires

The Black studies reader - Bobo, Jacqueline; Hudley, Cynthia; Michel, Claudine (Routledge, 2004)
Black studies emerged from the tumultuous social and civil rights movements of the 1960s and empowered African Americans to look at themselves in new ways and pass on a dignified version of Black history. However, it also enriched traditional disciplines in profound and significant ways. Proponents of Black and ethnic studies confronted the false notion that scholarly investigations were objective and unbiased explorations of the range of human knowledge, history, creativity, artistry, and scientific discovery. As they protested against hegemonic notions like universal psychology and re-evaluated canonical texts in literature, a new model of academic inquiry evolved: one committed to serving a range of populations, that critiqued traditional politics, culture, and social affairs, and worked with activist energy for the transformation of the existing social order. With an all-star cast of contributors, The Black Studies Reader takes on the history and future of this multi-faceted academic field. Topics include Black feminism, cultural politics, Black activism, lesbian and gay issues, African American literature and film, education, and religion. This authoritative collection takes a critical look at the current state of Black studies and speculates on where it may go from here.
Keywords: afro-féminisme; amériques; approches et analyses; féminisme islamique; histoire et politique; identités LGBTQIA2+; militance; outils; ouvrages de références; racisme; ressource en ligne; régions géographiques; sexualité; système colonial; systèmes d'oppression; thématiques; états-unis